Jurisprudence and legal theory - "Pillai, P.S. Atchuthen" (Lucknow, 1985)
This standard work incorporates all important developments in the subject. Prof. Pillai has elicited from amidst the explosive volume of case-law available today, the basic jurisprudential principles and presented them in a precise form. This comprehensive book covers the complete syllabus of jurisprudence and Legal Theory of the different Indian Universities and every possible aspect of present day jurisprudence and the diverse and varied theories of the great ancient and modern jurists have been covered.
Keywords: Law